Functionally Improved Mesenchymal Stem Cells to Better Treat Myocardial Infarction - Zhi Chen; Long Chen; Chunyu Zeng; Wei Eric Wang (Hindawi Limited, 2018)
Myocardial infarction (MI) is one of the leading causes of death worldwide. Mesenchymal stem cell (MSC) transplantation is considered a promising approach and has made significant progress in preclinical studies and clinical trials for treating MI. However, hurdles including poor survival, retention, homing, and differentiation capacity largely limit the therapeutic effect of transplanted MSCs. Many strategies such as preconditioning, genetic modification, cotransplantation with bioactive factors, and tissue engineering were developed to improve the survival and function of MSCs. On the other hand, optimizing the hostile transplantation microenvironment of the host myocardium is also of importance. Here, we review the modifications of MSCs as well as the host myocardium to improve the efficacy of MSC-based therapy against MI.